Europäisierung des Rechts Deutsch-Ungarisches Kolloquium Budapest 2007 - Heun, Werner; Lipp, Volker (Universitätsverlag Göttingen, 2008)
The series is published by the Law Faculty of the Georg-August-University, making events at the Faculty of an interested public.